A Possible Four Month Periodicity in the Activity of FRB 20240209A - Arpan Pal (The Astrophysical Journal Letters)
Fast radio bursts (FRBs) are millisecond-duration radio transients from distant galaxies. While most FRBs are singular events, repeaters emit multiple bursts, with only two—FRB 121102 and FRB 180916B—showing periodic activity (160 and 16 days, respectively). FRB 20240209A, discovered by CHIME-FRB, is localized to the outskirts of a quiescent elliptical galaxy ( z = 0.1384). We discovered a periodicity of  ∼126 days in the activity of the FRB 20240209A, potentially adding to the list of extremely rare periodic repeating FRBs. We used autocorrelation and Lomb–Scargle periodogram analyses, validated with randomized control samples, to confirm the periodicity. The FRB’s location in an old stellar population disfavors young progenitor models, instead pointing to scenarios involving globular clusters, late-stage magnetars, or low-mass X-ray binaries. Though deep X-ray or polarimetric observations are not available, the localization of the FRB and a possible periodicity point to progenitors likely to be a binary involving a compact object and a stellar companion or a precessing/rotating old neutron star.